Influencia de soluciones irrigantes en los procedimientos de endodoncia regenerativa - Doris Raquel, Villamarín Monta (2023)
ABSTRACT: The influence of irrigating solutions in regenerative endodontic procedures is a substantial issue taking into account that irrigation is a significant step, considering that it is capable of determining the success of the treatment, this is attributed to the fact that it is not only a matter of sanitizing and disinfecting the root canal, This is attributed to the fact that it is not only a matter of sanitizing and disinfecting the root canal, but also the type of irrigating to be used, since its chemical properties intervene either positively or negatively in the union, proliferation and differentiation of stem cells, important elements for treating immature necrotic permanent teeth through the regeneration of dentinopulpal tissue by means of revascularization. The objective of this research has been to analyze the influence of irrigating solutions in regenerative endodontic procedures, by establishing the characteristics of the main solutions used, determining comparatively which solutions have a positive and negative influence. The bibliographic evidence indicates that the most commonly used solutions for irrigation are 1.5% sodium hypochlorite (NaOCl) due to its antimicrobial efficacy as it is an excellent bactericide and organic matter solvent, followed by a final irrigation with 17% ethylenediaminetetraacetic acid (EDTA) being the irrigating that stands out most for promoting the expression of growth factors, mainly TGF-β1 (growth factor beta-1), which favors the survival and differentiation of stem cells, contributing significantly to the regeneration of dentinopulpal tissue. On the other hand, cytotoxic effects of irrigating solutions on stem cells have been detected, mainly at NaOCl concentrations higher than 1.5%.